Development of Salmonella-based DNA vaccine against respiratory syncytial virus. - Suhaimi, Siti Syazani (2011)
Human respiratory syncytial virus (HRSV) remains a major respiratory pathogen responsible for severe pulmonary disease in young children, immunodeficient patients and the elderly. Although these complications are public health concern worldwide, an effective RSV vaccine is still unavailable. In 1960s the formalin-inactivated (FI) RSV vaccine failed due to an imbalanced Th2-biased immune response as enhanced diseases in vaccinated infants were induced upon infection with RSV. It is believed that an effective and safe vaccine needs to elicit a balanced immune response, including high levels of HRSV-specific neutralizing antibodies, Th1/Th2 CD4+ T-cells, CD8+ T-cells, and preferably strong mucosal IgA to provide complete protection against RSV In the present study a Salmonella-based DNA vaccine against HRSV was designed. The G glycoprotein which has been implicated as the attachment protein of RSV is a potentially important target for protective antiviral immune response. While, cholera toxin B subunit (CTB) gene which acts as genetic adjuvant is an effective strategy to enhance induction of both humoral and cellular immune responses. Therefore, firstly the RSV G epitope regions including residues 125-226 was cloned along with the CTB gene into pVAX1, a mammalian expression vector, resulting a DNA vaccine vector designated as pVAX1-CTB/G. In vitro expression of CTB-G was confirmed by transfection of the recombinant pVAX1-CTB/G into COS-7 cells as the expected protein band was observed in western blot analysis. Secondly, the pVAX1-CTB/G vector was transformed into Salmonella typhi Ty21a as a vehicle for DNA vaccine delivery. The immunogenicity and protective efficacy of recombinant Salmonella harbouring the pVAX1-CTB/G was assessed in BALB/c mice model before and after RSV challenge. The capacity of pVAX1-CTB/G to enhance humoral (Th2), cellular (Th1), as well as mucosal responses were evaluated by measurement of cytokines and immunoglobulin levels in serum of immunized BALB/c mice before and after challenge with RSV. Results indicated that the developed vaccine could significantly enhance Th1 (IL-2, IFN-γ) and Th2 (IL-4, IL-10) cytokines response compared to control group. While, antibody isotype immunoglobulin analysis revealed that the DNA vaccine induced significant concentrations of systemic antibody (IgG1, IgG2a) as well as mucosal (IgA) in vaccinated mice compared to control group. Moreover, the obtained ratio of Th1/Th2 was desirable (~1) suggesting that Salmonella carrying pVAX1-CTB/G is potent vaccine candidate against HRSV. Lymphocyte proliferation assay showed that cell mediated immunity was also significantly increased in response to this vaccine. Finally,significant reduction of HRSV titer and presence of less viral RNA in the lung tissues of vaccinated mice compared to control confirmed the efficacy of Salmonella vaccine harboring pVAX1-CTB/G.